MAPPING THE NEXUS BETWEEN ENTREPRENEURSHIP AND LEGAL FRAMEWORKS: A BIBLIOMETRIC ANALYSIS OF GLOBAL RESEARCH TRENDS (2016–2025) (Proceeding of SINERGY, 2026)
This phenomenon indicates that entrepreneurship can no longer be understood merely as an individual economic activity but rather as a practice embedded in diverse legal and institutional configurations across countries. This research uses a quantitative approach thru through bibliometric analysis with the bibliographic coupling method, utilizing VOSviewer software to map the intellectual connections between documents, authors, journal sources, organizations, and countries based on the similarity of references used. The analysis results indicate that the structure of the literature is dominated by an institutional approach that positions law as a factor that simultaneously limits and facilitates entrepreneurship, with certain works serving as key conceptual nodes in the global research network. Furthermore, the findings reveal a concentration of knowledge production in certain countries and institutions, particularly in Western Europe and North America, reflecting geographical disparities in the development of entrepreneurship theory and policy. The analysis of journal sources also shows epistemic fragmentation between entrepreneurship studies and law, where interdisciplinary integration is still relatively limited. Overall, the results of this study affirm that the relationship between entrepreneurship and the legal framework forms a field of study that is institutional, contextual, and dynamic and opens up space for future research development that is more critical, polycentric, and interdisciplinary in responding to global economic and regulatory changes.